Rating Issues in Fault Tolerant PMSM - Raminosoa, Tsarafidy; Gerada, Christopher; Othman, Md Nazri (Electric Machines and Drives Conference, 2009. IEMDC '09. IEEE International, 2009)
The necessary reliability of a safety critical drive system is often partly achieved by using fault tolerant electrical machines. Although there are various degrees as to what types of faults and to the duration the machine has to tolerate, these generally include open and short circuit winding faults. There are numerous published literatures on the design of fault tolerant machines as well as on control algorithms used to maintain drive operation with an incurred fault. This paper is set to look at the effects of various fault tolerant control methods on the losses in three and five phase surface mount Permanent Magnet (PM) machines when in fault tolerant operation in order to be able to choose the correct rating for such conditions.